2014
DOI: 10.1007/s00787-014-0577-0
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of ADHD and incontinence in children

Abstract: ADHD and incontinence are common childhood disorders which co-occur at much higher rates than expected by chance. The aim of this review was to provide an overview both of the comorbidity of nocturnal enuresis (NE), daytime urinary incontinence (DUI) and faecal incontinence (FI) in children with ADHD; and, vice versa, of the co-occurrence of ADHD in children with NE, DUI and FI. Most clinical studies have focussed on the association of ADHD and NE. Population-based studies have shown that children with DUI hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 114 publications
2
82
0
3
Order By: Relevance
“…Since previous studies have identified a high comorbidity with (neuro)psychological and/or motor difficulties [3,4], this might play a role in the pathogenesis, especially in refractory cases. Psychological problems are even more common in children with daytime incontinence [2,5]. This is the first study excluding the children with daytime incontinence.…”
Section: Introductionmentioning
confidence: 96%
“…Since previous studies have identified a high comorbidity with (neuro)psychological and/or motor difficulties [3,4], this might play a role in the pathogenesis, especially in refractory cases. Psychological problems are even more common in children with daytime incontinence [2,5]. This is the first study excluding the children with daytime incontinence.…”
Section: Introductionmentioning
confidence: 96%
“…Areas of the brain such as the insula, the anterior cingulate cortex, and the prefrontal cortex are responsible for bladder control and monitoring 9 and have been implicated in ADHD and LUTD. 8 Hyde et al 10 considered enuresis during childhood a premorbid developmental marker of schizophrenia. In a group of patients with schizophrenia, 21% had enuresis during childhood versus 11% of their siblings and 7% of healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, between 20 and 30 % of the children with nocturnal enuresis have at least one psychological/psychiatric disorder, which is twofold the rate of children without nocturnal enuresis [12]. ADHD is the most prevalent and the most investigated comorbid psychological disorder [13,14]. Research on other psychological disorders may be less, but they are of at least equal importance.…”
Section: Nocturnal Enuresismentioning
confidence: 99%